Mixed convective flow and heat transfer of hybrid nanofluid impinging obliquely on a vertical cylinder. Issue 1 (31st December 2022) - Abbasi, Aamar; Farooq, Waseh; Mabood, F.
Abstract : Flow and heat transportation in hybrid nanofluid, impinging obliquely on a vertical cylinder, are investigated numerically in this communication. Silver Ag and aluminium oxide A l 2 O 3 nanoparticles having stable and relatively high thermal conductivity, with pure water as base fluid, are used in the analysis. The non-linear coupled partial differential equations are transformed into ordinary differential equations using suitable transformations. An implicit finite difference method is used to approximate the velocities and temperature for particular values of the various parameters and their effects are emphasised graphically. The tabular data are documented to compare the heat transfer rate for pure water silver/water nanofluid, aluminium/water nanofluid and ( silver + aluminium ) / water hybrid nanofluid. It is observed that heat transfer rate increases by increasing the curvature of the stretching cylinder and solid volume fraction of nanoparticles and for hybrid nanofluid it has a larger magnitude than that of water, Ag nanofluid and A l 2 O 3 nanofluid.